National health practitioner informatics system - Mamvura, Artwell (Midlands State University, 2017)
ICT tools are continuously changing business processes while the Zimbabwe’s public health sector still lags behind. The commercial industry has completely evolved because of e-Commerce business models but an e-Health strategy has not yet been implemented in the health sector. The need for a tool to track the areas in the country with critical shortages of public health care professionals and ease manipulation of health practitioner’s data stirred the development of the National Health Practitioner Informatics System (NHPIS). The NHPIS system is a health informatics system that allows ease querying, updating, deleting, inserting of health practitioners’ data. The term current system was used to refer to the existing system.